Necesidades de capacitación de profesionales unidocentes costarricenses para el desarrollo del pensamiento científico en el estudiantado - Ibarra-Vargas, Esteban Francisco (Universidad de Costa Rica, 2022)
The purpose of this article was to present some of the main results of a study carried out with Costa Rican single-teacher professionals, which focused on diagnosing their training needs to strengthen pedagogical mediation in relation to the development of scientific thinking in elementary school students. The data collection was carried out during the first quarter of the year 2021. The methodological approach used was the qualitative descriptive type, in which knowledge related to pedagogical mediation and the development of scientific thought in the single-teacher school was addressed, as well as its importance for students and rural communities. A group of thirty single-teacher professionals participated, who completed a qualitative survey as a diagnosis. The instrument was validated by a team of six experts. The analysis of the information allowed to contrast the results with the theory to identify the teacher training needs related to the object of study. Among the main results, the need to strengthen teacher training processes in terms of rural education, uni-teaching, and the development of scientific thinking skills of the student body stands out, considering the curricular provisions of the Ministry of Public Education. In addition to this, the importance of training single-teacher professionals in the following aspects related to pedagogical mediation is highlighted: learning by projects, scientific inquiry, and curricular integration, which presented varied results in terms of their knowledge, application and need for training.